Estudio de factibilidad de una alternativa de pago con reconocimiento facial en estaciones de Transmilenio, Bogotá. (2021)
Facial recognition is a branch of artificial intelligence that evolves rapidly and is being implemented in different sectors from telecommunications to the financial sector, offering new opportunities for improvement in companies, for this reason, through this article, the different variables are studied. take into account when carrying out a payment system with facial recognition in TransMilenio stations, from the analysis of the processes and actors involved in the collection system to the determination of the feasibility of the proposed project.